2014
DOI: 10.1002/path.4289
|View full text |Cite
|
Sign up to set email alerts
|

A core microRNA signature associated with inducers of the epithelial-to-mesenchymal transition

Abstract: Although it is becoming clear that certain miRNAs fulfil a fundamental role in the regulation of the epithelial-to-mesenchymal transition (EMT), a comprehensive study of the miRNAs associated with this process has yet to be performed. Here, we profiled the signature of miRNA expression in an in vitro model of EMT, ectopically expressing in MDCK cells one of seven EMT transcription factors (SNAI1, SNAI2, ZEB1, ZEB2, TWIST1, TWIST2 or E47) or the EMT inducer LOXL2. In this way, we identified a core subset of der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 55 publications
4
75
0
Order By: Relevance
“…This was highlighted by several DMRs targeting the MIR200 family (MIR200a, MIR200b, MIR200c, MIR141, MIR429) in UCS [43]. We found that CADs were located in MIR200b-MIR200a-MIR429’s promoter region (4 kb upstream of MIR200b), whereas in MIR200c-MIR141, SADs were localized in enhancer regions as predicted by chromHMM [41] (Figure 7 A ).…”
Section: Resultssupporting
confidence: 60%
“…This was highlighted by several DMRs targeting the MIR200 family (MIR200a, MIR200b, MIR200c, MIR141, MIR429) in UCS [43]. We found that CADs were located in MIR200b-MIR200a-MIR429’s promoter region (4 kb upstream of MIR200b), whereas in MIR200c-MIR141, SADs were localized in enhancer regions as predicted by chromHMM [41] (Figure 7 A ).…”
Section: Resultssupporting
confidence: 60%
“…Molecularly, these cells are similar to basal breast cancer cells, originating from the same precursor [53]. However, with over expression of Snail, they manifest a claudin-low phenotype with upregulation of epithelial to mesenchymal (EMT) features [55, 56]. These cells with negligible expression of claudin 3, 4 or 7 and E-cadherin [49], are widely used to study EMT and known to cluster with the claudin-low patients and cell lines [55, 56].…”
Section: Resultsmentioning
confidence: 99%
“…However, with over expression of Snail, they manifest a claudin-low phenotype with upregulation of epithelial to mesenchymal (EMT) features [55, 56]. These cells with negligible expression of claudin 3, 4 or 7 and E-cadherin [49], are widely used to study EMT and known to cluster with the claudin-low patients and cell lines [55, 56]. Here we found that while parental HMLE cells (clusters with basal/basal A) have Rab25 protein expression, the introduction of Snail completely suppresses Rab25 protein (Figure 3C upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…The epithelial to mesenchymal transition (EMT) is an important cellular phenotypic change in which polarized, immotile epithelial cells acquire the motile mesenchymal phenotype. EMT is regulated by miRNAs (12,13) that promote tumor invasion and metastasis and allow tumor cells to escape apoptosis (14).…”
mentioning
confidence: 99%